Penyuluhan Upaya Peningkatan Penggunaanalatkontrasepsi Pada WUS Dalam Menurunkan Prevalensi Stunting Di Desa Pariksinomba Kecamatan Dolok Sanggul Tahun 2024 - Sihite, Helprida; Simamora, Debora Natalia (Jurnal Masyarakat Indonesia (Jumas), 2025)
The high rate of stunting in Indonesia is a public health challenge that requires special attention, especially intervention at the family level. One effort to prevent stunting is through optimal pregnancy spacing, which can be achieved by increasing the use of contraceptives in women of childbearing age. The aim is to evaluate the effectiveness of education in increasing understanding and use of contraceptives as a stunting prevention strategy. The method used involves intensive counseling to groups of women of  childbearing age in several areas with a high prevalence of stunting. The research results showed an increase in participants' knowledge and understanding of the benefits of contraception in supporting maternal and child health, as well as a reduction in the incidence of short-term pregnancies, which is a risk factor for stunting. The conclusion is that education about contraception is effective in promoting public awareness regarding the importance of spacing pregnancies as an effort to prevent stunting in Indonesia.